Developmental and degenerative modulation of GABAergic transmission in the mouse hippocampus. Issue 47 (21st September 2015) - Kim, Jinwook; Son, Yeonghoon; Kim, Juhwan; Lee, Sueun; Kang, Sohi; Park, Kyunghwan; Kim, Sung‐Ho; Kim, Jong‐Choon; Kim, Jeongtae; Takayama, Chitoshi; Im, Heh‐In; Yang, Miyoung; et al.
Abstract: γ‐Aminobutyric acid (GABA) is the main inhibitory neurotransmitter involved in synaptic plasticity. GABAergic transmission is also implicated in developmental and degenerative processes in the brain. The goal of the present study was to understand the developmental and degenerative regulation of GABAergic transmission in the mouse hippocampus by examining changes in GABA receptor subunit mRNA levels and GABA‐related protein expression during postnatal development of the hippocampus and trimethyltin (TMT)‐induced neurodegeneration in the juvenile (postnatal day [PD] 24) and adult hippocampus (PD 56). During postnatal development, the mRNA levels of GABA A receptor (GABAA R) subunits, including α1, α4, β1, β2, and δ ; GABA B receptor (GABAB R) subunit 2; and the expression of GABA‐related proteins, including glutamic acid decarboxylase, vesicular GABA transporter (VGAT), and potassium chloride cotransporter 2 increased gradually in the mouse hippocampus. The results of seizure scoring and histopathological findings in the hippocampus revealed a more pronounced response to the same administered TMT dose in juvenile mice, compared with that in adult mice. The mRNA levels of most GABA receptor subunits in the juvenile hippocampus, excluding GABAA R subunit β3, were dynamically altered after TMT treatment. The mRNA levels of GABAA R subunits γ2 and δ decreased significantly in the adult hippocampus following TMT treatment, whereas the level of GABAB R subunit 1 mRNA increased significantly. Among the GABA‐related proteins, only VGAT decreased significantly in the juvenile and adult mouse hippocampus after TMT treatment. In conclusion, regulation of GABAergic signaling in the mouse hippocampus may be related to maturation of the central nervous system and the degree of neurodegeneration during postnatal development and TMT‐induced neurodegeneration in the experimental animals.